The development of mobile payment in China-A study of Alipay - DENG, WEIJIE (2018)
Mobile payment is now a mature technology based on mobile phones. China owns the largest penetration rate in terms of mobile payment compared to other developed countries such as USA, South Korea even though the development of m-payment in China did not start until 2011. Besides, the underlying technology and application scenarios are different from other countries. Inspired by the gap, this paper aims to study the development of mobile payment in China by studying the third party mobile payment vendor giant – Alipay through qualitative methods and to figure out what factors contribute to its success. By means of the concept of digital ecosystem, summarization of past literatures, theoretical models, SWOT and PEST analysis, it turns out that various factors contribute to the success of Alipay, internal factors such as thoughtful strategies, external factors such as economy, technology trend. Besides, Alipay’s future is far more complicated than imagination. The evolution of Alipay may also reflect the importance of building a long-standing business. Overall, the success of m-payment in China is not occasional, but a result of various aspects which could offer implication for other businesses.